Circular Permutated PQQ‐Glucose Dehydrogenase as an Ultrasensitive Electrochemical Biosensor. (28th December 2021) - Guo, Zhong; Smutok, Oleh; Johnston, Wayne A.; Ayva, Cagla Ergun; Walden, Patricia; McWhinney, Brett; Ungerer, Jacobus P. J.; Melman, Artem; Katz, Evgeny; Alexandrov, Kirill
Abstract: Protein biosensors play an increasingly important role as reporters for research and clinical applications. Here we present an approach for the construction of fully integrated but modular electrochemical biosensors based on the principal component of glucose monitors PQQ‐glucose dehydrogenase (PQQ‐GDH). We designed allosterically regulated circular permutated variants of PQQ‐GDH that show large (>10‐fold) changes in enzymatic activity following intramolecular scaffolding of the newly generated N‐ and C termini by ligand binding domain/ligand complexes. The developed biosensors demonstrated sub‐nanomolar affinities for small molecules and proteins in colorimetric and electrochemical assays. For instance, the concentration of Cyclosporine A could be measured in 1 μL of undiluted blood with the same accuracy as the leading diagnostic technique that uses 50 times more sample. We further used this biosensor to construct highly porous gold bioelectrodes capable of robustly detecting concentrations of Cyclosporine A as low as 20 pM and retained functionality in samples containing at least 60 % human serum. Abstract : Circular permutation of PQQ‐glucose dehydrogenase creates an artificial allosteric enzyme controlled by ligand binding to N‐ and C‐terminal domains. The developed biosensors demonstrated sub‐nanomolar affinities for small molecules and proteins in colorimetric and electrochemical assays.